2017
DOI: 10.1038/s41598-017-12251-4
|View full text |Cite
|
Sign up to set email alerts
|

Airway Changes after Cleft Orthognathic Surgery Evaluated by Three-Dimensional Computed Tomography and Overnight Polysomnographic Study

Abstract: Cleft lip and palate is the most common congenital craniofacial anomaly. Up to 60% of these patients will benefit from cleft orthognathic surgery, which consists primarily of maxillary advancement and mandibular setback to address midface retrusion and relative mandibular protrusion, respectively. It is believed that maxillary advancement can enlarge the airway whilst mandibular setback can reduce the airway, but this has not previously been quantified for cleft patients undergoing orthognathic surgery. This u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 30 publications
1
24
0
3
Order By: Relevance
“…Several studies have measured surface areas and volumes of the nasopharynx, oropharynx, and hypopharynx following MA using CT scans. 11 , 19 22 However, there is no clear consensus as to the morphological changes seen following MA. 11 , 21 , 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have measured surface areas and volumes of the nasopharynx, oropharynx, and hypopharynx following MA using CT scans. 11 , 19 22 However, there is no clear consensus as to the morphological changes seen following MA. 11 , 21 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…The majority of published studies focus primarily on the structural changes to the airway and their impact on patients with obstructive sleep apnea. 11 , 13 , 16 , 28 , 29 To the best of our knowledge, the anatomical changes of the velum studied on CT scans have yet to be reported. Patients with no history of CP have the ability to compensate for the structural changes following MA, which prevents any adverse effects on velopharyngeal closure function and speech.…”
Section: Discussionmentioning
confidence: 99%
“…The cleft lip and palate can take to the reduction of the nasal cavity dimensions, with great probability of occurring oral breathing, fact observed in the studied sample, once approximately 80% of the individuals presented oral breathing. It is worth to highlight that the maxillary advancement can also have effect on breathing, because there is an increase in the dimension of the middle third of the face, together with the volume increase of the pharyngeal airway space and, consequently, breathing improve (29) . Such findings were the same found in this sample once for the majority of the cases, the breathing was presented nasal after the surgery, as expected.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study by Chang et al [68] examined the airway changes in cleft patients who received maxillary advancement and mandibular setback treatments by not only CBCT but also polysomnographic examination. Regarding the airway changes after orthognathic surgery, it was found that there was no significant difference in sleep-related respiratory functions, but the snoring index was improved.…”
Section: Airway Problemsmentioning
confidence: 99%
“…In an analysis of the USA National Inpatient Samples Database (2012-2013), the rate of emergence for any kind of infectious complication following orthognathic surgery was reported as 7.4% in patients with a craniofacial anomaly and 0.6% in those without a craniofacial anomaly [78]. Recent studies reported rates of from 0to 13.92% for infections emerging after orthognathic surgery in cleft patients without any craniofacial anomaly [61,62,68,70]. In the study that obtained a high rate of incidence as 13.92% despite 5 days of routine antibiotics usage, the authors emphasized the importance of oral hygiene, team collaboration, and patient cooperation [70].…”
Section: Infectionmentioning
confidence: 99%